Permanences and alterations in the occupied city: cartography of napoleonic Seville - Navarro-de-Pablos, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The beginning of the second decade of the 19th century in Seville was marked by the French occupation. The uniqueness of the Andalusian capital is determined by the intensity of the use of public space as an “official” showcase for the opposing powers. This explains how, in the space of a year, the city went from holding processions against the entry of French troops into Spain to welcoming them with finery. By means of the cartographic restitution of the local chronicles, the aim is to reveal the relationship between the logics of power and urban form that define a singular way of occupying public space.